2018
DOI: 10.1021/acs.chemmater.8b02295
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Phase Transitions and Thermally Persistent Local Distortions in CsPbBr3 Quantum Dots

Abstract: The optoelectronic properties of CsPbX3 quantum dots (where X = Cl, Br, or I) are influenced by both their local and average structures. Variable-temperature synchrotron X-ray diffraction measurements of CsPbBr3 quantum dots show that the temperatures for both the orthorhombic-to-tetragonal (50 °C < T γ‑β < 59 °C) and tetragonal-to-cubic (108 °C < T β‑α < 117 °C) phase transitions of the average structure are depressed relative to their temperatures in bulk CsPbBr3. Simultaneously, pair distribution function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 32 publications
5
91
0
Order By: Relevance
“…There is also a significant loss in intensity as the sample is slowly heated and again when the temperature is reduced back to 100 K. This loss is likely due to damage from the electron beam over time and the formation of Pb nanoparticles within the lattice 41 . XRD has been previously performed on CsPbBr 3 using powder diffraction 14 and HR-TEM [20][21][22][23][24][25][42][43][44] . However, from this result alone, it has been difficult to determine the difference between the orthorhombic, tetragonal and cubic structural lattices of CsPbBr 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also a significant loss in intensity as the sample is slowly heated and again when the temperature is reduced back to 100 K. This loss is likely due to damage from the electron beam over time and the formation of Pb nanoparticles within the lattice 41 . XRD has been previously performed on CsPbBr 3 using powder diffraction 14 and HR-TEM [20][21][22][23][24][25][42][43][44] . However, from this result alone, it has been difficult to determine the difference between the orthorhombic, tetragonal and cubic structural lattices of CsPbBr 3 .…”
Section: Resultsmentioning
confidence: 99%
“…CsPbBr 3 has been shown to undergo two structural phase changes in the single-crystal form: the orthorhombic (Pbnm) to tetragonal (P4/mbm) phase transition at 361 K and the tetragonal (P4/mbm) to (Pm3m) cubic transition at 403 K, both of which occur far above room temperature 18,19 . However, these transition temperatures are lower for CsPbBr 3 quantum dots and powders 20,21 . Our understanding of both the electronic and crystalline structures of nanocrystalline CsPbBr 3 , particularly below these transition temperatures, is still lacking 17 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In reality, the picture of a perfect defect free bulk that is dynamically fluctuating along particular octahedral tilting paths is very likely to simplistic. Recent studies indicate the prevalence of ferroelastic twin boundaries [16,17,[39][40][41] in halide perovskites. Bertlotti et al [16] demonstrated that the apparent tetragonal and cubic phases, as probed using x-ray diffraction, can result from domains of twinned orthorhombic a − a − c + variants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been increasing evidence that the high temperature cubic phase of many perovskites is not, in fact, cubic on a local scale [12][13][14][15][16][17]. Instead, the cubic phase emerge as a result of static and/or dynamic disorder.…”
Section: Introductionmentioning
confidence: 99%